2017
DOI: 10.1021/acs.jpca.7b09721
|View full text |Cite
|
Sign up to set email alerts
|

Heptavalent Actinide Tetroxides NpO4 and PuO4: Oxidation of Pu(V) to Pu(VII) by Adding an Electron to PuO4

Abstract: The highest known actinide oxidation states are Np(VII) and Pu(VII), both of which have been identified in solution and solid compounds. Recently a molecular Np(VII) complex, NpO(NO), was prepared and characterized in the gas phase. In accord with the lower stability of heptavalent Pu, no Pu(VII) molecular species has been identified. Reported here are the gas-phase syntheses and characterizations of NpO and PuO. Reactivity studies and density functional theory computations indicate the heptavalent metal oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Thus, the NU–OO complex can be described as [(NU) 2+ (O 2 ) 2– ], a neutral uranium nitride-peroxide species with U in the oxidation state +V. The structure and bonding of [(NU) 2+ (O 2 ) 2– ] are reminiscent of those of actinide tetraoxides (UO 4 and PuO 4 ), , which were computed to be [(An +V O 2 ) + (O 2 ) − ] species as well. As shown in Figure , the bonding between NU and O 2 is dominated by the orbital interaction between the empty U 5f π orbital of UN and the antibonding π* orbitals of O 2 , which results in an increased U 5f π orbital energy and decreased π* orbital energy.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Thus, the NU–OO complex can be described as [(NU) 2+ (O 2 ) 2– ], a neutral uranium nitride-peroxide species with U in the oxidation state +V. The structure and bonding of [(NU) 2+ (O 2 ) 2– ] are reminiscent of those of actinide tetraoxides (UO 4 and PuO 4 ), , which were computed to be [(An +V O 2 ) + (O 2 ) − ] species as well. As shown in Figure , the bonding between NU and O 2 is dominated by the orbital interaction between the empty U 5f π orbital of UN and the antibonding π* orbitals of O 2 , which results in an increased U 5f π orbital energy and decreased π* orbital energy.…”
Section: Results and Discussionmentioning
confidence: 99%
“…There is a continuous interest in synthesizing new compounds with highest OSs, of metallic elements in particular, including the lanthanoids and actinoids 10–25 . Previous experimental and theoretical studies have shown that the highest OSs of the 3d, 4d, 5d (and 4f) elements exhibit “volcano”‐type variations, what had already been noted by Langmuir in 1919 26 .…”
Section: Introductionmentioning
confidence: 90%
“…Gibson et al recently showed that upon reducing Pu V O 4 , Pu is oxidized to form the Pu VII O 4 À ion. 23 Zaitsevskii and co-workers performed relativistic DFT calculations on AnO 4 (An = Pu, Am, and Cm) molecules and found that the ground states have dioxide-superoxide-like structures [AnO 2 ](O 2 ) with all three actinoids in OS = V. 56 Further theoretical work on AnO 3 , AnO 4 , An 2 O n (An = Pu, Am) and on PuAmO n found the most stable form as PuAmO 4 . 57 However, because of the complexity of electron correlation and spin-orbit coupling in the Pu, Am, and Cm containing molecules, systematic investigations on the OS assignment of actinoid elements in AnO 4 appear still necessary at higher levels of sophistication.…”
mentioning
confidence: 99%
“…Compared to the flourishing uranyl peroxides, their transuranic counterparts are still in infancy, despite their strategic importance in the nuclear industry. Specifically, neptunium (Np) and plutonium (Pu) are two of the most studied transuranic elements, reported to form various compounds with oxide, sulfate, phosphate, arsenate, and other oxyanions, However, the Np and Pu actinyl peroxide chemistry is largely unexplored. There are only one structurally characterized neptunyl peroxide polymeric compounds with a Np 24 unit, some mononeptunyl peroxide complexes, such as Ca 2 [NpO 2 (O 2 ) 3 ]·9H 2 O, and [NpO 2 (O 2 ) 3 ] polyhedra .…”
Section: Introductionmentioning
confidence: 99%